Analisis Dampak Program Makan Bergizi Gratis (MBG) terhadap Partisipasi Siswa dalam Pembelajaran Pendidikan Jasmani: Studi Kasus di SD Negeri 1 Bebesen - Nopri Abadi Miko; Budiman; Birrul Walidaini; Arda Tonara (LSM Catimore dan Sahabat Jl. Paya Ilang/Pertamina Desa Lemah Burbana, Takengon, Aceh Tengah 24552, 2026)
Quality education is influenced not only by pedagogical aspects but also by students’ physical readiness, which is closely related to nutritional status. This study aims to analyze the implementation of the Free Nutritious Meal Program (MBG) and its impact on student participation in Physical Education learning at SD Negeri 1 Bebesen. The research employed a qualitative approach with a case study design. Data were collected through observation, semi-structured interviews, and documentation, and analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. Data validity was ensured through source and technique triangulation as well as member checking. The findings indicate an increase in students’ average attendance from 85% to 93% after the implementation of the program, along with a decrease in the number of students absent due to illness or fatigue. These changes are described based on observational and documentation data within the qualitative case study context. Observational results reveal improvements across all participation indicators, including active engagement in warm-up activities, endurance during core exercises, enthusiasm in games, and responsiveness to teacher instructions. Thematic analysis identified four main themes: increased physical energy, enhanced enthusiasm and motivation, active participation in physical activities, and improved attendance consistency. These findings suggest that the MBG program contributes not only to students’ physical well-being but also to psychological readiness, thereby supporting the effectiveness of Physical Education learning. Integrating school nutrition policies with activity-based learning represents a holistic approach to improving health-oriented educational quality.